In situ growing of ZIF-8 crystals into TiO2 micro columnar films - Juan J. Romero-Guerrero; Francisco G. Moscoso; Said Hamad; Gloria P. Moreno; Víctor Rico; Ángel Barranco Quero; Tânia Lopes-Costa; José M. Pedrosa (Next Materials)
This study proposes a fast and simple method for the in situ growth of metal-organic frameworks (MOFs) on metal oxide substrates as an alternative to the traditional approaches of using gold substrates and self-assembled monolayers (SAMs). As a case study, zeolitic imidazolate framework 8 (ZIF-8) crystals were grown in micro columnar TiO2 films through simple alternate and successive immersions of the TiO2 films into solutions containing the MOFs precursors. The growth process of the MOF crystals in the interstitial spaces between the TiO2 columns was investigated by varying the metal-to-ligand ratio (1:2, 1:4, and 1:8) and by employing modulating agents such as triethylamine. It was found that the optimal deposition of ZIF-8 occurred when using a higher excess of ligand and the addition of triethylamine after a controlled number of immersion cycles. These results were obtained by using glancing angle X-ray diffraction (GAXRD) and scanning electron microscopy-energy-dispersive X-ray spectroscopy (SEM-EDS) as characterization techniques. Additionally, a density functional theory (DFT) study as well as Fourier-transform infrared spectroscopy (FTIR) and GAXRD experiments were conducted to elucidate the nucleation process. It was concluded that the starting point is the formation of a covalent bond between the Zn cations and the TiO2 on the metal oxide surface after immersion of the film into a Zinc (II) nitrate solution, allowing for the formation of MOF nuclei once the film is subsequently immersed in the 2-methylimidazole solution. The results demonstrate the feasibility of in situ growth of MOF crystals onto metal oxide structures by a layer-by-layer strategy, offering a promising alternative to conventional methods.